Ovarian Seromucinous (Endocervical-Type Mucinous and Mixed Cell-Type) Tumor: A Case Report - Jui-Chi Lee; Yao-Ching Hung; Lian-Shung Yeh; Wei-Chun Chang (Elsevier, 2005)
Objective: Ovarian tumors are commonly encountered in clinical practice. Epithelial ovarian cancers account for the majority of female ovarian neoplasms. Some uncommon ovarian mucinous tumors have recently been termed "seromucinous" tumors because they exhibit both serous and mucinous features. Case Report: A 27-year-old female patient presented with a 2-month history of a palpable abdominal mass. Ultrasonography and computed tomography revealed a huge multilocular, solid pelvic cyst. Following staging surgery, pathological sections showed that the tumor was composed of a mixture of endocervical-type mucinous, serous, endometrioid, squamous, and undifferentiated cells. An ovarian seromucinous tumor was diagnosed. The neoplastic cells were located mainly within the ovarian epithelium with only focal stromal invasion. Metastatic implants were found in the pelvic peritoneum. The patient received six courses of chemotherapy after surgery and has been regularly followed. Conclusion: Seromucinous tumors can be classified from atypical proliferative tumors to invasive carcinomas. Death related to this kind of tumor is rare. The tumors are not common, and their clinical behavior is not as aggressive as other types. Prognostic factors have been studied, including morphologic cellular atypia, tumor necrosis, mitotic index, and depth of tumor invasion. Adjuvant therapy is necessary for patients with poor prognostic factors.